Compostagem de resíduos biodegradáveis e seus efeitos na produção da alface - Ferreira, Daianni Ariane da Costa (Universidade Federal Rural do Semi-Árido, 2016)
The increase in production of consumer goods brought increased generation of municipal solid waste. This subject has been working for several areas of knowledge, sanitation, environment, social integration that take into account screening processes, recycling of materials and energy use. Composting has been an alternative to recycling organic waste using microorganisms to transform organic matter into organic compound which can be used in orchards, gardens and agriculture. The aim of this work to encourage the implementation of the composting process with municipal solid waste and its effects on lettuce fertilization. The first stage of the research was developed in the courtyard of the Recycling Association for Community Living - ACREVI, Mossoró-RN, between September and December 2015 a stack of conical shape was mounted whose size 2.0m base 1 6 m high and 2 m in diameter. We evaluated the physical, chemical and biological properties of the compound produced with tree pruning, food waste and manure. The second stage of the research was conducted in a protected environment in the west campus of the Federal Rural University of Semi-Arid (UFERSA) in Mossoró-RN, between February and March 2016. It was used the vegetable lettuce type Crespo, seeded in the tray and transplanted 16 days after sowing. The experimental design was a randomized complete block design with three replications and five treatments, and evaluated the effects of five combinations of the organic compound produced in the first stage, referring to the 20 proportions; 40; 60; 80 and 100% mixed with coconut fiber substrate. the growth variables were evaluated, absorption of nutrients, production and lettuce quality produced using the composting of organic waste. This study allowed the development of a natural process for the treatment of organic solid waste for organic fertilization of lettuce. In the composting process, the mixture of three organic sources favored the production of the compound with excellent degree of ripeness and free from chemical and microbiological contaminants. In the lettuce, the addition of increasing doses of organic compost influenced the increase of lettuce growth, demonstrating the viability of organic fertilizer on the basis of environmental and food safety
Composting of biodegradable waste and its effects on lettuce production
Keywords: Manejo de resíduos sólidos; Nutriente; Hortaliças; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO